csi 3125, axiomatic semantics, page 1 axiomatic semantics the assignment statement statement...

57
CSI 3125, Axiomatic Semantics, page 1 Axiomatic semantics The assignment statement Statement composition The "if-then-else" statement The "while" statement Narrowing and widening • Termination Two diversions The greatest common divisor The "if-then" statement Points to discuss:

Upload: amy-cunningham

Post on 31-Dec-2015

227 views

Category:

Documents


0 download

TRANSCRIPT

CSI 3125, Axiomatic Semantics, page 1

Axiomatic semantics

• The assignment statement• Statement composition• The "if-then-else" statement• The "while" statement• Narrowing and widening• Termination• Two diversions• The greatest common divisor• The "if-then" statement

Points to discuss:

CSI 3125, Axiomatic Semantics, page 2

Program verification

Program verification includes two steps.

1. Associate a formula with every meaningful step of the computation.

2. Show that the final formula logically follows from the initial one through all intermediate steps and formulae.

CSI 3125, Axiomatic Semantics, page 3

What is axiomatic semantics?

• Axiomatic semantics of assignments, compound statements, conditional statements, and iterative statements has been developed by Professor C. A. R. Hoare.

• The elementary building blocks are the formulae for assignments and conditions.

• The effects of other statements are described by inference rules that combine formulae for assignments (just as statements themselves are combinations of assignments and conditions).

CSI 3125, Axiomatic Semantics, page 4

The assignment statement

Let be a logical formula that contains variable v.

v e is a formula which we get from

when we replace all occurrences of

variable v with expression e.

CSI 3125, Axiomatic Semantics, page 5

Replacement, an example

Before replacement:

h >= 0 & h <= n & n > 0

h 0 0 >= 0 & 0 <= n & n > 0

after replacement

CSI 3125, Axiomatic Semantics, page 6

Another example

m == min( 1 <= i & i <= k–1: ai ) &

k–1 <= N

k k+1 m == min( 1 <= i & i <= (k+1) – 1: ai ) &

(k+1)–1 <= N

m == min( 1 <= i & i <= k: ai ) & k <= N

CSI 3125, Axiomatic Semantics, page 7

The axiom for the assignment statement

{v e } v = e {}

Example:

{ 0 >= 0 & 0 <= n & n > 0 }

x = 0;

{ x >= 0 & x <= n & n > 0 }

CSI 3125, Axiomatic Semantics, page 8

Two small puzzles

{ ??? } z = z + 1; { z <= N }

{ a > b } a = a – b; { ??? }

CSI 3125, Axiomatic Semantics, page 9

Statement composition

ASSUME THAT

{´ } S ´ {´´ }

and

{´´ } S ´´ {´´´ }

CONCLUDE THAT

{´ } S ´ S ´´ {´´´ }

In other words:

{´ } S ´ {´´ } S ´´ {´´´ }

CSI 3125, Axiomatic Semantics, page 10

A more complicated example

x = 0; f = 1;while (x != n) { x = x + 1; f = f * x;}

We want to prove that

{ f == x! }x = x + 1;f = f * x;

{ f == x! }

CSI 3125, Axiomatic Semantics, page 11

Let's apply the inference rule for composition.

´ is f == x!

´´´ is f == x!

S ´ is x = x + 1;

S ´´ is f = f * x;

The factorial

CSI 3125, Axiomatic Semantics, page 12

We need to find a ´´ for which we can prove:{ f == x! } x = x + 1;

{´´ }f = f * x; { f == x! }

Observe that f == x! f == ((x + 1) – 1)!

and therefore f == (x – 1)! x x + 1 f == x!That is:{ f == x! } x = x + 1; {f == (x – 1)! }

´ ´´S ´

The factorial (2)

CSI 3125, Axiomatic Semantics, page 13

Now, let us observe that

f == (x – 1)! f * x == (x – 1)! * x == x!

So, we have

f == x! f f * x f == (x – 1)!

That is,

{f == (x – 1)! } f = f * x; {f == x! }

´´ ´´´S ´´

The factorial (3)

QED

CSI 3125, Axiomatic Semantics, page 14

The "if-else" statement

ASSUME THAT

{ & } S´ {}

and

{ & } S´´ {}

CONCLUDE THAT

{} if ( ) S ´ else S ´´ {}

Both paths through the if-else statement establish the same fact . That is why the whole conditional statement establishes this fact.

CSI 3125, Axiomatic Semantics, page 15

The statementif ( a < 0 ) b = -a; else b = a;

makes the formula b == abs(a) true.Specifically, the following fact holds:

{true}if ( a < 0 ) b = -a; else b = a;{ b == abs(a) }

Here: is true is b == abs(a) is a < 0

Also: S´ is b = -a;S´´ is b = a;

"if-else", an example

CSI 3125, Axiomatic Semantics, page 16

We will consider cases. First, we assume that is true:

true & a < 0 a < 0 – a == abs(a)Therefore, by the assignment axiom:

{– a == abs(a)} b = -a; {b == abs(a)}

Similarly, when we assume , we get this:

true & a < 0 a 0 a == abs(a)Therefore:

{a == abs(a)} b = a; {b == abs(a)}

"if-else", an example (2)

CSI 3125, Axiomatic Semantics, page 17

This shows that both S´ and S´´ establish the same condition:

b == abs(a)Our fact has been proven:

{true}if ( a < 0 ) b = -a; else b = a;{ b == abs(a) }

In other words, our conditional statement computes abs(a). It does so without any preconditions: "true" means that there are no restrictions on the initial values of a and b.

"if-else", an example (3)

CSI 3125, Axiomatic Semantics, page 18

The "while" statement

A loop invariant is a condition that is true immediately before entering the loop, stays true during its execution, and is still true after the loop has terminated.

ASSUME THAT

{ & } S {}

[That is, S preserves .]CONCLUDE THAT

{ } while ( ) S { & }

provided that the loop terminates.

CSI 3125, Axiomatic Semantics, page 19

The factorial again...

x = 0; f = 1;while ( x != n ) {x = x + 1;f = f * x;

}

Assume for now that n ≥ 0. After computingx = 0; f = 1;

we have f == x! because it is true that 1 == 0!We showed earlier that{ f == x! } x = x + 1; f = f * x; { f == x! }

CSI 3125, Axiomatic Semantics, page 20

Now, is f == x! is x != n is x == n

Using the inference rule for "while" loops:

{ f == x! }while ( x != n ) { x = x + 1; f = f * x;}{ f == x! & x == n}

The factorial again... (2)

CSI 3125, Axiomatic Semantics, page 21

Notice that

f == x! & x == n f == n!

This means two things:{ true } x = 0; f = 1; { f == x! }

AND{ f == x! } while ( x != n ) {

x = x + 1; f = f * x;}

{ f == n!}

The factorial again... (3)

CSI 3125, Axiomatic Semantics, page 22

In other words, the program establishes f == n! without any preconditions on the initial values of f and n, assuming that we only deal with n ≥ 0.

The axiom for statement composition gives us:{ true } x = 0; f = 1;

while ( x != n ) { x = x + 1; f = f * x;}

{ f == n!}

So: this program does compute the factorial of n.

The factorial again... (4)

CSI 3125, Axiomatic Semantics, page 23

Our reasoning agrees with the intuition of loop invariants: we adjust some variables and make the invariant temporarily false, but we re-establish it by adjusting some other variables.

{ f == x! } x = x + 1; {f == (x – 1)! }the invariant is "almost true"

{f == (x – 1)! } f = f * x; {f == x! }the invariant is back to normal

This reasoning is not valid for infinite loops:the terminating condition & is never reached, and we know nothing of the situation following the loop.

The factorial again... (5)

CSI 3125, Axiomatic Semantics, page 24

Narrowing and widening

ASSUME THAT

´

and

{} S { }

CONCLUDE THAT

{´ } S { }

ASSUME THAT

{} S { }

and

´

CONCLUDE THAT

{ } S { ´ }

These rules can be used to narrow a precondition, or to widen a postcondition.

CSI 3125, Axiomatic Semantics, page 25

n! is computed, for any nonnegative n, with true as the precondition (it is always computed successfully);

So, n! will in particular must be computed successfully if initially n == 5.

Narrowing and widening, a small example

CSI 3125, Axiomatic Semantics, page 26

A larger example (in a more concise notation)

{ N >= 1 } { N >= 1 & 1 == 1 & a1 == a1 } i = 1; s = a1;

{ N >= 1 & i == 1 & s == a1 } { N >= 1 & s == a1 + … + ai } INVARIANTwhile ( i != N ) {

{ N >= 1 & s == a1 + … + ai & i != N }i = i + 1;

{ N >= 1 & s == a1 + … + ai–1 & i – 1 != N }s = s + ai;

{ N >= 1 & s == a1 + … + ai }}

{ N >= 1 & s == a1 + … + ai & i == N } { N >= 1 & s == a1 + … + aN }

CSI 3125, Axiomatic Semantics, page 27

• We have shown that this program computes the sum of a1, ..., aN.

• The precondition N >= 1 is only necessary to prove termination.

A larger example (2)

CSI 3125, Axiomatic Semantics, page 28

Termination

• Proofs like these show only partial correctness.– Everything is fine if the loop stops.– Otherwise we don't know (but the program

may be correct for most kinds of data).• A reliable proof must show that all loops in the

program are finite.• We can prove termination by showing how each

step brings us closer to the final condition.

CSI 3125, Axiomatic Semantics, page 29

Once again, the factorial…

• Initially, x == 0.

• Every step increases x by 1, so we go through the numbers 0, 1, 2, ...

• n >= 0 must be found among these numbers.

• Notice that this reasoning will not work forn < 0: the program loops.

CSI 3125, Axiomatic Semantics, page 30

A decreasing function

• A loop terminates when the value of some function of program variables goes down to 0 during the execution of the loop.

• For the factorial program, such a function could be n – x. Its value starts at n and decreases by 1 at every step.

• For summation, we can take N – i.

CSI 3125, Axiomatic Semantics, page 31

Multiplication by successive additions

{ B >= 0 & B == B & 0 == 0} FOR TERMINATIONb = B; p = 0;{ b == B & p == 0 } { p == A * (B – b) } INVARIANTwhile ( b != 0 ) {

p = p + A;{ p == A * (B – (b – 1)) }b = b - 1;{ p == A * (B – b) }

}{ p == A * (B – b) & b == 0} { p == A * B }The loop terminates, because the value of the variable b goes down to 0.

CSI 3125, Axiomatic Semantics, page 32

Two diversions

Prove that the sequencep = a; a = b; b = p;

exchanges the values of a and b :

{ a == A & b == B }p = a; a = b; b = p;

{ b == A & a == B }

The highlights of a proof:{ a == A & b == B } p = a;{ p == A & b == B } a = b;{ p == A & a == B } b = p;{ b == A & a == B }

CSI 3125, Axiomatic Semantics, page 33

x = x + y;

y = x - y;

x = x - y;

Two diversions (2)

Discover and PROVE the behaviour of the following sequence of statements for integer variables x, y:

CSI 3125, Axiomatic Semantics, page 34

{x == X & y == Y }

{x + y == X + Y & y == Y } x = x + y;

{x == X + Y & y == Y }

{x == X + Y & x - y == X } y = x - y;

{x == X + Y & y == X }

{ x - y == Y & y == X } x = x - y;

{ x == Y & y == X }

Two diversions (3)

CSI 3125, Axiomatic Semantics, page 35

The greatest common divisor

{ X > 0 & Y > 0 }a = X; b = Y;{ } what should the invariant be?while ( a != b ) { & a != b } {if ( a > b ) { & a != b & a > b }

a = a - b;else { & a != b & (a > b) }

b = b - a;}{ & (a != b) }{ GCD( X, Y ) == a }

CSI 3125, Axiomatic Semantics, page 36

We will need only a few properties of greatest common divisors:

GCD( n + m, m ) == GCD( n, m )GCD( n, m + n ) == GCD( n, m )

The first step (very formally):

{ X > 0 & Y > 0 } { X > 0 & Y > 0 & X == X & Y == Y }

a = X; b = Y;

{ a > 0 & b > 0 & a == X & b == Y }

GCD (2)

CSI 3125, Axiomatic Semantics, page 37

When the loop stops, we geta == b & GCD( a, b ) == a

We may want this condition in the invariant:a == b & GCD( X, Y ) == GCD( a, b )

At the beginning of the loop, we have:{ a > 0 & b > 0 & a == X & b == Y } {a > 0 & b > 0 & GCD( X, Y ) == GCD( a, b ) }

So, the invariant could be this:a > 0 & b > 0 & GCD( X, Y ) == GCD( a, b )

GCD (3)

CSI 3125, Axiomatic Semantics, page 38

We should be able to prove that{a > 0 & b > 0 & GCD(X, Y) == GCD(a, b) & a != b}while ......{a > 0 & b > 0 & GCD(X, Y) == GCD(a, b)}

The final condition will bea > 0 & b > 0 &GCD(X, Y) == GCD(a, b) & a == b

and this will implyGCD( X, Y ) == a

GCD (4)

CSI 3125, Axiomatic Semantics, page 39

The loop consists of one conditional statement.

Our proof will be complete if we show this:

{a > 0 & b > 0 & GCD(X, Y) == GCD(a, b) & a != b}

if ( a > b )a = a - b;

elseb = b - a;

{a > 0 & b > 0 & GCD(X, Y) == GCD(a, b)}

GCD (5)

CSI 3125, Axiomatic Semantics, page 40

Consider first the case of a > b.

{a > 0 & b > 0 &GCD(X, Y) == GCD(a, b) & a != b & a > b }

{a – b > 0 & b > 0 & GCD(X, Y) == GCD(a – b, b)}

a = a - b;

{a > 0 & b > 0 & GCD(X, Y) == GCD(a, b)}

GCD (6)

CSI 3125, Axiomatic Semantics, page 41

Now, the case of a > b.

{a > 0 & b > 0 & GCD(X, Y) == GCD(a, b) & a != b & (a > b) }

{a > 0 & b – a > 0 & GCD(X, Y) == GCD(a, b – a)}

b = b - a;

{a > 0 & b > 0 & GCD(X, Y) == GCD(a, b)}

GCD (7)

CSI 3125, Axiomatic Semantics, page 42

Both branches of if-else give the same final condition. We will complete the correctness proof when we show that the loop terminates.We show how the value of max( a, b ) decreases at each turn of the loop.

Let a == A, b == B at the beginning of a step. Assume first that a > b:

max( a, b ) == A,so a – b < A, b < A,

therefore max( a – b, b ) < A.

GCD (8)

CSI 3125, Axiomatic Semantics, page 43

Now assume that a < b:

max( a, b ) == B,

b – a < B, a < B,

therefore max( a, b – a ) < B.

Since a > 0 and b > 0, max( a, b ) > 0.

This means that decreasing the values of a, b cannot go forever.

QED

GCD (9)

CSI 3125, Axiomatic Semantics, page 44

The "if" statement

ASSUME THAT

{ & } S { }

and

&

CONCLUDE THAT

{ } if ( ) S { }

CSI 3125, Axiomatic Semantics, page 45

We will show the following:

{ N > 0 }

k = 1; m = a1;while ( k != N ) { k = k + 1;

if ( ak < m ) m = ak;}

{ m == min( 1 <= i & i <= N: ai ) }

An example with "if"

CSI 3125, Axiomatic Semantics, page 46

Loop termination is obvious:

the value of N – k goes down to zero.

Here is a good invariant: at the kth turn of the loop, when we have already looked at a1, ..., ak, we know that

m == min( 1 <= i & i <= k : ai ).

Initially, we have this:{ N > 0 } k = 1; m = a1;{ k == 1 & m == a1 } { k == 1 & m == min( 1 <= i & i <= k : ai ) }

Minimum

CSI 3125, Axiomatic Semantics, page 47

We must prove the following:

{ m == min( 1 <= i & i <= k : ai ) & k != N }k = k + 1;if ( ak < m ) m = ak;{ m == min( 1 <= i & i <= k : ai ) }

Minimum

CSI 3125, Axiomatic Semantics, page 48

{ m == min( 1 <= i & i <= k : ai ) & k != N }

{ m == min( 1 <= i & i <= (k + 1) – 1: ai ) & (k + 1) – 1 != N }

k = k + 1;

{ m == min( 1 <= i & i <= k – 1: ai ) & k – 1 != N }

Note that k – 1 != N ensures the existence of ak.

Minimum (2)

CSI 3125, Axiomatic Semantics, page 49

This remains to be shown:

{ m == min( 1 <= i & i <= k – 1: ai ) & k – 1 != N }

if ( ak < m ) m = ak;

{ m == min( 1 <= i & i <= k: ai ) }

The fact we will use is this:

min( 1 <= i & i <= k: ai ) ==min2( min( 1 <= i & i <= k – 1: ai ), ak )

Minimum (3)

CSI 3125, Axiomatic Semantics, page 50

We will consider two cases of the conditional statement.

First, (ak < m).

{m == min(1 <= i & i <= k – 1: ai ) &k – 1 != N & (ak < m)}

{m == min2(min( 1 <= i & i <= k – 1: ai ), ak )}

{m == min(1 <= i & i <= k: ai )}

Minimum (4)

CSI 3125, Axiomatic Semantics, page 51

Now, ak < m.

{m == min(1 <= i & i <= k – 1: ai ) &k – 1 != N & ak < m}

{ak == min2( min( 1 <= i & i <= k – 1: ai ), ak )}

{ak == min(1 <= i & i <= k: ai )}

m = ak;

{m == min(1 <= i & i <= k: ai )}

So, the body of the loop preserves the condition

m == min( 1 <= i & i <= k: ai )

Minimum (5)

CSI 3125, Axiomatic Semantics, page 52

Now, the whole loop works as follows:

{ m == min( 1 <= i & i <= k: ai ) }while ( k != N ) }

k = k + 1; if ( ak < m ) ak = m;}

{ m == min( 1 <= i & i <= k: ai ) & k == N } { m == min( 1 <= i & i <= N: ai ) }

All in all, we have shown that our program finds the minimum of N numbers, if only N > 0.

QED

Minimum (6)

CSI 3125, Axiomatic Semantics, page 53

Yet another "while" loop

{ B > 0 } FOR TERMINATIONb = 1; p = A;while ( b != B ) {

b = b + 1;p = p * A;

}{ ??? }

Examples

CSI 3125, Axiomatic Semantics, page 54

Yet another "while" loop (2)

{ B > 0 & 1 == 1 & A == A} FOR TERMINATIONb = 1; p = A;{ b == 1 & p == A } { p == A ** b } INVARIANTwhile ( b != B ) {

b = b + 1;{ p == A ** (b - 1) }p = p * A;{ p == A ** b }

}{ p == A ** b & b == B} { p == A ** B }The loop terminates: the value B - b goes down to 0.

Examples

CSI 3125, Axiomatic Semantics, page 55

{ N > 0 } FOR TERMINATIONk = 1;while ( k != N ) {

if ( Ak > Ak+1 )

{ p = Ak; Ak = Ak+1; Ak+1 = p; } k = k + 1; }{ ??? }

Another example with "if"Examples

CSI 3125, Axiomatic Semantics, page 56

{ N > 0 } FOR TERMINATIONk = 1;{ Ak == max( 1 <= i & i <= k: Ai ) } INVARIANTwhile ( k != N ) { { Ak == max( 1 <= i & i <= k: Ai ) & k != N } if ( Ak > Ak+1 ) { p = Ak; Ak = Ak+1; Ak+1 = p; } { Ak+1 == max( 1 <= i & i <= k+1: Ai ) } k = k + 1; { Ak == max( 1 <= i & i <= k: Ai ) }}

{Ak == max( 1 <= i & i <= k: Ai ) & k == N } {AN == max( 1 <= i & i <= N: Ai ) }

Another example with "if" (2)Examples

CSI 3125, Axiomatic Semantics, page 57

{Ak == max( 1 <= i & i <= k: Ai ) & k != N }

case 1: Ak > Ak+1

{ Ak == max( 1 <= i & i <= k: Ai ) & k != N & Ak > Ak+1}

p = Ak; { p > Ak+1 }

Ak = Ak+1; { p > Ak }

Ak+1 = p; { Ak+1 > Ak }

{ Ak+1 == max( 1 <= i & i <= k+1: Ai ) }

case 2: Ak <= Ak+1

{ Ak == max( 1 <= i & i <= k: Ai ) & k != N & Ak <= Ak+1 } { Ak+1 == max( 1 <= i & i <= k+1: Ai ) }

Another example with "if" (3)Examples